Non-halogenated solvent-processed ternary-blend solar cells via alkyl-side-chain engineering of a non-fullerene acceptor and their application in large-area devices. Issue 20 (13th May 2020) - Lee, Taeho; Oh, Sora; Rasool, Shafket; Song, Chang Eun; Kim, Dongwook; Lee, Sang Kyu; Shin, Won Suk; Lim, Eunhee
Abstract : Ternary-blend organic solar cells based on a novel asymmetric non-fullerene acceptor (T2-OEHRH) processed from a non-halogenated solvent exhibit impressive PCEs of 12.10% and 9.32% in small- and large-area devices, respectively. Abstract : Solution processability is one of the advantages of organic solar cells (OSCs). However, most high-efficiency OSCs are prepared using hazardous chlorinated solvents for the deposition of photoactive layers. The replacement of non-halogenated solvents with eco-friendly green solvents for photoactive materials is urgently required. Herein, we have developed a novel asymmetric T2-OEHRH, which is modified from the symmetric T2-ORH . The introduction of asymmetric alkyl side chains onto rhodanine end groups can effectively suppress excessive self-aggregation/crystallization and substantially improve solubility without sacrificing optoelectrical properties. Therefore, ternary-blend OSCs based on PTB7-Th :EH-IDTBR :T2-OEHRH processed using a non-halogenated solvent system exhibit a uniform and favorable morphology and give a high power conversion efficiency (PCE) of 12.10%. More importantly, we demonstrate an impressive PCE of 9.32% for large-area NFA-OSCs (substrate size = 100 cm 2 and aperture size = 55.5 cm 2 ) prepared via D-bar coating in air. To our knowledge, this PCE is the highest reported to date for NFA-based large-area OSC modules processed from a non-halogenated solvent. This asymmetric alkyl-chain engineering strategy can be exploited to develop high-performance large-area NFA-OSCs with eco-friendly solvent processing.